Comparative effectiveness and safety of atorvastatin versus rosuvastatin among patients with ischemic stroke or transient ischemic attack: a national registry-based observational studyResearch in context - Jianhua Zhao; Xinya Li; Xue Xia; Xue Tian; Qin Xu; Xiaoli Zhang; Ruobing Tian; Xia Meng; Anxin Wang (EClinicalMedicine, 2025)
Summary: Background: Atorvastatin and rosuvastatin are the most widely used statins in patients with ischemic stroke or transient ischemic attack (TIA). However, evidence on their effectiveness and safety during actual use is scarce. This study aims to compare the effectiveness and safety of initiating atorvastatin versus rosuvastatin among patients with ischemic stroke or TIA. Methods: This observational study was based on the Third China National Stroke Registry (CNSR-III), which recruited consecutive adult patients with ischemic stroke or TIA within 7 days from the onset of symptoms to enrollment from August 2015 to March 2018. This study identified 3322 adults aged ≥18 years who had a pre-stroke modified Rankin Scale (mRS) score of 0 and initiated atorvastatin or rosuvastatin on the day of onset. The primary outcome was the ideal outcome, as defined by a mRS score of 0, at 3 months. The secondary outcomes included the ideal outcome at discharge, at 6 months, and at 12 months, along with 12-month stroke recurrence, all-cause mortality, cardiovascular mortality, and major adverse cardiovascular events. Findings: A total of 3322 eligible patients were identified, with 2605 initiating atorvastatin and 717 initiating rosuvastatin. The proportion of patients achieving an ideal outcome, as defined by a modified Rankin Scale of 0, was 44.63% in rosuvastatin initiators, significantly higher than 41.46% in atorvastatin initiators, with a relative rate of 1.12 (95% confidence interval 1.03, 1.22). Also, a greater percentage of rosuvastatin initiators attained the ideal outcome at discharge and at 6 months, compared with atorvastatin initiators. Regarding other secondary outcomes, no statistically significant difference was observed. Interpretation: Compared with atorvastatin, rosuvastatin was associated with a potentially higher proportion of patients attaining a mRS score of 0 among patients with ischemic stroke or TIA who initiate atorvastatin or rosuvastatin, which was not yet sufficient to guide clinical practice. Further research is needed to validate these findings. Funding: This work was supported by National Key Research and Development Program of China (2022YFC2502400, 2022YFC2502404), Beijing Natural Science Foundation Haidian original innovation joint fund (L222123), and Youth Innovation Fund of Beijing Neurosurgical Institute (2025 Reform and Development–Youth 15).